"Just one of many donors": Canada's engagement with civil society in Afghanistan. Issue 3 (2nd September 2019) - Apsani, Rishita; Baruah, Bipasha; Shaw, Jennifer
ABSTRACT: Canada's entry into Afghanistan as a NATO ally was widely considered a necessary military venture, but Canadian operations during the reconstruction period that ensued were criticized as having tarnished Canada's reputation on the international stage. Canada's history as a peacekeeping nation and its perceived middle power status did initially allow it to act as a mediator between the Afghan government, local actors, and the international community. However, our research discovered that Canada did not fully understand the dynamics of the established civil society structures in Afghanistan, nor the ways in which they influence local politics. A limited understanding of "civil society" among Canadian officials and disproportionate focus on professionalized NGOs as its most legitimate representative meant that local civil society groups in Afghanistan and the role they could play to establish democratic structures were largely ignored. By complementing knowledge synthesis of existing scholarly and policy literature with interviews with Canadian and Afghan aid workers, this article examines the process of post-conflict rebuilding in Afghanistan, considering how neglecting Afghan civil society has resulted in less durable social structures. We also examine Canada's image as an international mediator, and identify new ways of assisting rebuilding processes to ensure more durable and peaceful outcomes.